ANALYSIS OF MODERN TRENDS OF OVERCOMING MANAGERIAL STEREOTYPES - T. N. Andropova (Вестник университета, 2020)
The preferences of employees of organizations in male and female leadership qualities, as well as in the choice between a male leader and a female leader have been studied. More specifically, three factors have been considered, which can influence on these preferences: gender of the employee, gender of the manager, and the ratio of men to women in the organization. In the process of research, the theory of congruency has been studied, which claims that there is a mismatch between the female gender role and the role of manager. The concept of tokenism has been analysed. Empirical studies show mixed support for the concept of tokenism. Indeed, there are studies confirming that numerical representation negatively correlates with discrimination. Using the theory of social roles, it has been concluded that women leaders suffer from shortcomings based on prejudices related to gender and managerial stereotypes. As a result of the study, the author comes to the conclusion that increasing the proportion of women leaders is an effective way to overcome managerial stereotypes.